IMPLEMENTING INTERACTIVE READING MODEL TO TEACH HORTATORY EXPOSITION TEXT TOTHE ELEVENTH GRADERS OF SMAN 1 SOOKO MOJOKERTO (RETAIN, 2014)
IMPLEMENTING INTERACTIVE READING MODEL TO TEACH HORTATORY EXPOSITION TEXT TO THE ELEVENTH GRADERS OF SMAN 1 SOOKO MOJOKERTO Arista Nurhayati English Department, Languages and Arts Faculty, State University of Surabaya, noorhayati16@yahoo.co.id Aswandi, Drs., M. Pd. English Department, Languages and Arts Faculty, State University of Surabaya, aswandi20@yahoo.com Abstrak Penelitian ini merupakan sebuah penelitian deskriptif kualitatif yang menggambarkan bagaimana guru menggunakan model membaca interaktif dalam pengajaran teks hortatory exposition pada siswa kelas XI di SMAN 1 Sooko Mojokerto dan bagaimana respon siswa pada saat mereka diajarkan membaca teks hortatory exposition menggunakan model membaca interaktif. Penelitian ini dilaksanakan di kelas XI IPA 6 di SMAN 1 Sooko Mojokerto pada semester kedua. Data penelitian diperoleh dari observasi kelas, kuesioner siswa, dan wawancara dengan guru yang bersangkutan. Kemudian, data tersebut dianalisis menggunakan tiga langkah, yaitu data reduksi, penyajian data, dan verifikasi. Hasil analisis menunjukkan bahwa guru menggunakan model membaca interaktif dalam pengajaran teks hortatory exposition dengan langkah-langkah berikut: mengenalkan judul, membekali siswa dengan struktur bahasa dan pengetahuan linguistic terkait, berkonsentrasi pada pelafalan dan pengenalan kata, mengajak siswa memprediksi arti kata baru nenggunakan kamus dan konteks, meminta siswa mentransfer informasi tersurat dan tersirat ke dalam bentuk tabel, bertanya pada siswa tentang opini dan perasaan mereka mengenai isi teks, dan melaksanakan latihan tambahan. Sedangkan respon siswa pada saat mereka diajarkan teks hortatory exposition dengan menggunakan model membaca interaktif menunjukkan hasil yang bagus dari sisi pengembangan kosakata, latihan pelafalan kata, dan kesempatan untuk berkomunikasi. Berdasarkan hasil penelitian, guru disarankan untuk memakai teks yang memenuhi kriteria kesesuaian isi dengan topic bahasan, mudah untuk dieksplorasi, dan layak sebagai bahan bacaan. Di samping itu, peneliti selanjutnya harus fokus pada penggunaan model membaca interakrif untuk mengajarkan genre teks yang berbeda dan pada level siswa yang berbeda pula. Kata Kunci: model membaca interaktif, teks hortatory exposition, respon siswa Abstract This study is a descriptive qualitative research which describes how the teacher implements interactive reading model to teach hortatory exposition text to the eleventh graders of SMAN 1 Sooko Mojokerto and how are the students’ responses when they are taught reading hortatory exposition text by using that model. This study was conducted on the second semester of XI science 6 in SMAN 1 Sooko Mojokerto. The data was collected from classroom observations, students’ questonnaires, and an interview with the teacher. Later, the data were analized in three steps: data reduction, data display, and verification. The result showed that the teacher implemented the interactive reading model to teach hortatory exposition in these steps: introducing the title/headline; preparing the students’ structure and linguistic feature; focusing on the students’ pronunciation and word recognition; asking the students to find out unknown words by using context and dictionary; requiring the students to transfer the message from the text into a table; asking the students’ opinion and feeling toward the text; and conducting follow-up activities. Meanwhile, the students’ responses toward the implementation of interactive reading model were good in terms of vocabulary improvement, pronunciation practice, and opportunity for communication. Based on the result of this study, the researcher suggests to the teacher to use the text which fulfils the criteria of suitability of content, exploitability, and readability. Besides, the next researchers should be concern to use the interactive reading model to teach the different kinds of text and the other levels of the student. Keywords: interactive reading model, hortatory exposition text, students’ responses INTRODUCTION Reading is the source of meaningful and comprehensible linguistic input that helps unconscious language acquisition. Anderson (2003:68) states that reading is a process of combining information from a text and the reader’s background knowledge to get meaning. In addition, Krashen (1981) in Lyutaya (2011:27) argues that effective reading skills are essential in the English as Foreign Language situation because of limited exposure to spoken English. Therefore, reading becomes one alternative which encourages students with more language exposure to written English. However, there are many reasons why getting students to read English texts is an important part of teacher’s job. Firstly, it is simply because students want to be able to read texts in English for some purposes, such as for careers, study purposes, or simply for entertainment. Besides, Harmer (1998:68) believes that reading texts also provide good models for English writing and opportunities to study language components such as vocabulary, grammar, punctuation, etc. Secondly, it is the objective of the Indonesian curriculum that students are expected to be able to communicate in English, in which “to communicate” means “to produce spoken and written English texts”. Thus, anything that teachers can do to help them speak and write English texts easily must be a good idea. Furthermore, the approach adopted by the Indonesian curriculum is literacy approach. This approach defines reading and writing to achieve social purposes in context of use. Therefore, the teaching of English to senior high school students addresses informative text in contexts of use on some kinds of texts, such as discussion and exposition. An exposition text is a kind of factual text that should be mastered by the eleventh graders of senior high school as they come in contact with maps, menus, guides, brochures, newspapers, magazines, and the internet in the daily life. Exposition texts being taught at school are divided into two: hortatory exposition and analytical exposition. In this occasion, the writer concerns only at the teaching of hortatory exposition. According to Street (2002:34), students often come to high school with limited experience with content area texts on the textbook such as exposition and explanation. Further, the writer discovers that students have been engaged in reading a narrative text. They are excited in reading an adolescent novel, connecting their prior knowledge to the new one, and clarifying misconceptions. But they do not know the strategic reading skills to learn more about their textbook. They become passive, with simply skimming over the foreign words and pictures, making no real connections between the exposition text and their own experience. To make students engaged in reading an exposition text, teachers need to step in and offer support for them. In this case, the teacher can use interactive reading model to teach reading hortatory exposition. Interactive reading is another type of reading model which combines the elements of both bottom-up and top-down models. Furthermore, Stanovich in Nunan (1998:67) claims that interactive reading model is superior because it deals with the lack of the other models, and allows for the deficiencies at one level to be exchanged for at another. This model also suggests that a reader processes a text by using information from several different sources in the same time. These sources can be phonological, lexical, syntactic, semantic, and discourse knowledge. In short, interactive reading model is accepted as the most comprehensible description of reading process. As a matter of fact, interactive reading model is still rarely used in the teaching of reading. The teacher is usually focuses on exploring the grammatical structure and language features of the text without considering the student’s prior knowledge of the topic. Often, the teacher leads the reading discussion by reading the following questions first. Then, skimming or scanning the information to answer the questions and seeing dictionary to find vocabulary meaning. But later, the teacher does not relate the topic with the students’ experiences or arguments. Consequently, the students understand how to find out the information to answer the questions but often find difficulties in guessing word meaning from the context or the knowledge they already know. Therefore, the teacher needs to emphasize not only bottom-up but also top-down reading process to help students activate their background knowledge. Eventually, the students will be able to develop their thinking in higher level of comprehension. Finally, the interactive reading model is appropriate to be applied in teaching reading hortatory exposition. First, it is simply because a hortatory exposition text contains vocabulary with a particular content area, so that the terms are usually different with the vocabulary in a narrative. Second, it gives students an opportunity to explore vocabularies related to the content area and make connection between their prior knowledge and those vocabularies. In addition, Brown (2001:299) states that recent studies on teaching reading have shown that a combination of top-down and bottom-up or interactive reading model is an important part in successful teaching methodology because both processes are essential. Thus, this study is conducted to answer these following questions: (1) how is the implementation of interactive reading model to teach reading hortatory exposition to the eleventh graders of SMAN 1 Sooko Mojokerto? and (2) how are students’ responses when they are taught reading hortatory exposition by implementing interactive reading model?. Based on the problem questions, the aims of this study was to describe the implementation of interactive reading model to teach reading hortatory exposition to the eleventh graders of SMAN 1 Sooko Mojokerto and to know the students’ responses when they are taught reading hortatory exposition by implementing interactive reading model. Types of Reading According to Brown (2001:312), classroom reading performance is defined into two: oral and silent reading. Oral reading is the act of reading aloud. It is often used to develop pronunciation practice because the reader’s mistakes can be corrected by another reader at once. It also helps students to develop skills of speech and communication. On the other hand, silent reading is an individual activity in which communication is not between one reader and another, but between an author and a reader. Furthermore, silent reading in the classroom performance is divided into two: intensive and extensive reading. The main aim of intensive reading is developing students’ ability to decode message by drawing on syntactic and lexical cues and emphasizing skill for recognition. Moreover, Anderson (2003:71) adds that intensive reading includes a short text added by textbook activities to develop comprehension or particular reading skills in which the textbooks mostly use intensive reading approach. Therefore, the activities deal with the reading materials and the teacher’s guidance. On the other hand, extensive reading purposes to achieve general understanding of longer text such as book, essays, long articles, novels, etc. It can be an alternative to make reading more interesting and joyful. Lyutaya (2011:26) and Ono, et.al. (2004:12) agree that in extensive reading, students read for information and pleasure, with primary purpose of obtaining a general understanding of literary ideas, learn reading strategies, acquire new vocabulary, and increase their English proficiency as they read a large quantity of material both inside and outside of the classroom. Finally, it can be said that in intensive reading activities, students are in the main exposed to short texts which are used to give typical example of text genres, or to provide the method for targeted reading strategy practice. While the goal of extensive reading, on the other hand, is to enrich students reading ability with large quantities of targeted language input with few or possibly no specific tasks. In short, the combination of both reading strategies will be a helpful strategy in reading comprehension. Level of Reading Comprehension Reading comprehension is an active process that must be developed if a learner wants to be a proficient reader. Comprehension is understand what is being said or read and understand what someone reads can be viewed according to the level of thinking. According to Berry (2005:1-2), when reading, the reader’s level of thinking usually related to understanding at three kinds of information. They are literal level which involves what the author is actually saying, interpretive level which deals with what the author means by what is said, and applied level which concerns with why the author says what he or she says. These levels of comprehension are what make a reader skilled. With that thought in mind, it has been shown that strong readers make good writers. Furthermore, the integration of good level of reading comprehension and continued exposure to the English language enables readers to be writers which are better in expressing themselves. The Stages of Teaching Reading Abbott (1981:95) and Brown (1994) in Correia (2006:17) agree that there should be three stages to the teaching of reading. The first phase is pre-reading discussion, which involves introducing the topic and preparing students for the text (Papalia, 1987:75). In addition, Abbott (1981:95) describes pre-reading activities like asking the students to read only the headings or the title to anticipate content, showing a picture or video to recall students’ description about the text they are going to read, and explaining generic structure, language features, and some vocabularies as keywords which the meaning is needed to understand the text. The second phase includes while-reading tasks, in which students are provided with a set of instructions to give them a purpose for reading and to serve as a guide for them as they read. Abbott (1981:96) describes the activities which sharp the students’ cognitive just like identifying the main idea, finding details, following a sequence, inferring opinion, accepting the author’s purpose and opinion, and knowing the generic structure and language features. The third phase includes post-reading exercises, in which students are given short comprehension questions, vocabulary work, opportunity for discussion of the topic and the author’s reasoning, and/or a summary writing assignment. Reading Processes: bottom –up or top-down? One side consists of experts who claim that the process of reading begins with letters and their sounds (phonics). They support bottom-up model to explain the reading process. Additionally, Harmer (2007:270) describes that in bottom-up processing, the reader focuses on individual words, phrases, cohesive devices, and understands the text by combining those detail parts to make a complete understanding. In other side, other experts who subscribe top-down model of the reading process believe reading as mainly